(FeMnNi)84(AlTi)16 high‑entropy alloy: correlation of microstructure, strengthening mechanisms and hardness at various conditions (As‑Cast, solution treated, aged) - Konakoglou, Kimon; Mathiou, C.; Georgatis, E.; Georgarakis, Konstantinos; Karantzalis, A. E. (Springer, 2022)
A (FeMnNi)84(AlTi)16 high-entropy alloy was produced by vacuum arc melting successfully. The microstructure of the as-cast state showed the existence of two FCC phases along with potential precipitates. The solution treatment response of the alloy for 2 h at 1150 °C and the effect of aging time at 750 °C in the microstructure and microhardness were also evaluated. It was observed that the solution treatment parameters were insufficiently low to dissolve the as-cast precipitates into the matrix. The double FCC matrix identified may be correlated with a solidification range and insufficient diffusion during the solidification process. The maximum hardness at 90 min aging time can be mainly attributed to the precipitation shearing mechanism in both matrix areas. The lower hardness value reported at 160 h aging time was estimated that it is derived by the change of the main strengthening mechanism from shearing to Orowan. The island-like precipitates that depleted Ti element from the Ni-rich intergranular area may be identified as a Ni2AlTi Heusler phase.
Keywords: High-entropy superalloys; Solidification; Heusler phases; Strengthening mechanisms